The impact of COVID-19 pandemic on travel behaviour of commuters in Makurdi metropolis. Issue 1 (1st January 2021) - Adeke, P. T.; Zava, A. E.; Etika, A.
Abstract: The outbreak of Corona Virus (COVID-19) in the 4th quarter of year 2019 at Wuhan city of China, and its rapid spread across the world necessitated the introduction of travel restriction policies by the federal and state governments of Nigeria. This was to help curtail the spread of the deadly disease. This study examined the travel behaviour of flouting commuters in Makurdi metropolis amidst the travel restriction policy during the lockdown period. About 496 questionnaires were administered to commuters travelling within the 16 km radius metropolis. Essential factors captured in the questionnaire included modal split and trip purposes as affected by socio-demographic characteristics of commuters such as; age, gender, marital status, level of education, etc. The findings of the study revealed that there was no statistically significant level of dependence of commuters' socio-demographic characteristics on modal split and trip destinations at 5% level of significance using contingency tables. The trend revealed that there were no obvious influential changes in the travel behaviour of commuters in Makurdi metropolis amidst the COVID-19 pandemic. It was recommended that concerned authorities should create more awareness about the outbreak of pandemics to help instil fear in commuters and discourage travelling to prevent wide spread. Also, distribution of palliatives to households during lockdown periods to enable them cope with the situation as they remain indoors, and deployment of law enforcement agents to streets and highways to stop commuters from travelling during lockdown periods to minimise the spread of communicable diseases were recommended.